2008
DOI: 10.1021/nl802398j
|View full text |Cite
|
Sign up to set email alerts
|

Control of InAs Nanowire Growth Directions on Si

Abstract: We report on control of growth directions of InAs nanowires on Si substrate. We achieved to integrate vertical InAs nanowires on Si by modifying initial Si(111) surface in selective-area metal-organic vapor phase epitaxy with flow-rate modulation mode at low temperature. Crosssectional transmission electron microscope and Raman scattering showed that misfit dislocation with local strains were accommodated in the interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
360
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 349 publications
(373 citation statements)
references
References 29 publications
11
360
2
Order By: Relevance
“…Among the III-V compounds, InAs has emerged as a narrow-band-gap semiconductor with very high electron mobility and a small electron effective mass, 5 which is particularly convenient for high-frequency electronic applications. 6 While bulk InAs crystallizes in cubic zinc-blende structure, it has been demonstrated that InAs nanowires can be grown in the wurtzite form.…”
Section: Introductionmentioning
confidence: 99%
“…Among the III-V compounds, InAs has emerged as a narrow-band-gap semiconductor with very high electron mobility and a small electron effective mass, 5 which is particularly convenient for high-frequency electronic applications. 6 While bulk InAs crystallizes in cubic zinc-blende structure, it has been demonstrated that InAs nanowires can be grown in the wurtzite form.…”
Section: Introductionmentioning
confidence: 99%
“…81 , 88 NW selective-area epitaxy (NW-SAE) seems a more promising approach for III-V integration on Si because it avoids the use of a catalyst nanoparticle, and instead uses a patterned oxide mask to control the location of III-V growth. 81 The disadvantage of these techniques is that they rely on Si(111) substrates to grow NWs in that direction. Recently, a template-assisted growth technique has been introduced that overcomes various NW growth limitations ( Figure 4d ).…”
Section: Integration Of Iii-v Semiconductors On Siliconmentioning
confidence: 99%
“…Vertical orientation of nanowires can be achieved on Si (1 1 1) substrates in very high yields [14][15][16]. In the case of catalyst-free growth, ordered arrays of nanowires can in principle be attained by employing a patterned SiO 2 mask [15,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%